Incidence, contributing factors and outcomes of birth injury among newborns in Africa: a systematic review of quantitative evidence protocol - Abera Mersha; Shitaye Shibiru (BMJ Open)
Introduction Birth injury is a significant public health problem in Africa, with a high incidence and associated mortality and morbidity. Systematic reviews that indicate the incidence, contributing factors and outcomes of birth injury in Africa provide valuable evidence to policy-makers and programme planners for improving prevention and treatment strategies. Therefore, this review is aimed to evaluate the incidence, contributing factors and outcomes of birth injury among newborns in Africa.Methods and analysis The data will be searched and extracted from JBI Database, Cochrane Database, MEDLINE/PubMed, CINAHL/EBSCO, EMBASE, PEDro, POPLINE, Proquest, OpenGrey (SIGLE), Google Scholar, Google, APA PsycInfo, Web of Science, Scopus and HINARI. Unpublished studies and grey literature will be searched from different sources. This systematic review will include quantitative observational studies, registry and census data, and experimental studies that report on the prevalence or incidence in Africa from 1 January 1990 to 30 September 2023. The Joanna Briggs Institute (JBI) quality appraisal checklist will be used to select eligible studies. Two researchers will independently appraise and extract the data from included studies and resolve discrepancies through discussion. Heterogeneity will be assessed using forest plots and the I2 statistic. If substantial heterogeneity is present, a random-effects model will be used to pool the data. Subgroup analyses will be used to explore the potential sources of heterogeneity. Publication bias will be assessed using funnel plots and Egger’s regression test. The software package used to conduct the meta-analysis will be JBI SUMARI. An association will be considered significant if the p<0.05.Ethics and dissemination Ethical clearance is not needed for this systematic review and the results will be shared with relevant stakeholders to maximise reach and impact.PROSPERO registration number CRD42023123637.